METHODOLOGY OF TECHNICAL-TACTICAL PREPARATION OF SHORT-DISTANCE RUNNERS IN ATHLETICS TRAINING - Sh.Khudaykulov (Journals Park Publishing, 2023)
The article describes the improvement of the problematic teaching technology of technical and tactical training of short-distance runners in athletics training through the ARIZ-ARIZ method.
Keywords: Short distance running